Nghiên cứu tác dụng của Permethrin tẩm màn chống sốt rét - Vũ, Thị Phan (2011)
Tác giả: Vũ Thị Phan, GS; Nguyễn Phước Hồng; Nguyễn Long Giang; Bùi Đình Bái; Trần Thị Hòa -- Từ khóa: Màn tẩm Permethrin; Permethrin tẩm màn; Phòng chống sốt rét ác tính